Measuring antigen-specific bactericidal responses to a multicomponent vaccine against serogroup B meningococcus - Giuliani, Marzia M.; Biolchi, Alessia; Serruto, Davide; Ferlicca, Francesca; Vienken, Kay; Oster, Philipp; Rappuoli, Rino; Pizza, Mariagrazia; Donnelly, John (Vaccine, 2010)
Serum bactericidal activity using human complement is the basis for established correlates of protection against invasive meningococcal disease. During the development of multicomponent protein-based vaccines against meningococcus B, it is necessary to measure antigen-specific bactericidal responses. This is not straightforward because each strain may be killed by antibodies to multiple antigens. We characterized a large panel of strains and, using a competitive inhibition SBA, we identified four strains that are each specifically killed by bactericidal antibodies to one of the major vaccine components. These strains provide a straightforward approach to demonstrate protective responses to each component of the vaccine and demonstrate that each of the antigens in the vaccine is sufficient to provide a potentially protective level of bactericidal activity.